Frustrated quantum magnets - Andrew Wibawa (2013)
A class of Frustrated Quantum Magnets (FQM) is investigated using the Stochastic Series Expansion (SSE) Quantum Monte Carlo (QMC) method. Such a model is relevant to a class of rare earth tetraboride materials that display multi stepped magnetization plateaus under external magnetic field. The Shastry-Sutherland lattice was used to represent the arrangement of magnetic ions in these materials.